2008
DOI: 10.3200/htps.86.4.3-17
|View full text |Cite
|
Sign up to set email alerts
|

Including Quality, Access, and Efficiency in Healthcare Cost Models

Abstract: The authors investigated cost models that incorporate quality, access, and efficiency to provide decision support for resource forecasting in the multi-billion-dollar U.S. Army health system. As the Army relocates thousands of troops, the medical system must plan for changes in demand; this study supports that effort. Loglinear cost models that include data envelopment analysis (DEA) efficiency scores were evaluated through ordinary least squares estimation, ridge regression, and robust regression, and serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Four years of data were used to make predictions for the next 2 years. Similarly, we found another article forecasting resources for US Army health care (25). That study used ordinary least squares estimation, ridge regression, and robust regression and concluded that, although all the models produced nearly the same estimates, ordinary least squares was desirable because it had the simplest interpretations.…”
Section: Discussionmentioning
confidence: 52%
“…Four years of data were used to make predictions for the next 2 years. Similarly, we found another article forecasting resources for US Army health care (25). That study used ordinary least squares estimation, ridge regression, and robust regression and concluded that, although all the models produced nearly the same estimates, ordinary least squares was desirable because it had the simplest interpretations.…”
Section: Discussionmentioning
confidence: 52%
“…Note that these specified data parameters are typical of government hospitals [48] and are often used as variables in MHS performance measurement and evaluation studies [3,4,19,21,22]. As shown in Table 1, the MHS input resources to be manipulated include EXP , ENROLL, and F T E, whereas the output resources are listed as RV U and QU AL.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…Ozcan et al [48] evaluated trends in hospital efficiency using longitudinal data. Fulton et al [22] proposed regression-based military hospital cost models that included DEA efficiency scores in addition to the variables of quality, access, and satisfaction. Nayar and Ozcan [44] provided a DEA comparison of Virginia hospitals in terms of efficiency and quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 1 describes the set of health system input and output variables selected for analyzing MHS performance. These output and input parameters are typical of government facilities (e.g., Ozcan and Bannick 1994;O'Neill et al 2008) and are routinely used as predictors of MHS performance (Fulton et al 2007(Fulton et al , 2008.…”
Section: Computational Experimentsmentioning
confidence: 99%
“…They used DEA and stochastic frontier analysis to identify the cost drivers for performance-based resource allocation. Then, Fulton et al (2008) proposed regression-based military hospital cost models that included DEA efficiency scores in addition to the variables of quality, access, and efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%